The effectiveness of an education program based on healthcare transition in adolescents with asthma: A randomized controlled trial - Dinç, Fatma; Yildiz, Dilek; Ercan, Nazli; Dinç, Fatma (Wiley, 2024)
Background: Adolescents diagnosed with asthma make a transition to adult care when they reach a certain age. Besides, these adolescents need specialized education for them to become autonomous, competent, and adult patients and gain the necessary knowledge and skills related to their disease. In this study, by using a prospective randomized controlled trial design, we evaluated the effectiveness of an education program based on healthcare transition provided to adolescents diagnosed with asthma. Methods: After obtaining the consent of adolescents and their parents, 52 adolescents aged between 14 and 18 years who were diagnosed with asthma were randomly assigned to the intervention group (individual four face-to-face and six online education sessions) or the control group (standard care). The primary outcome was the differences between the Transition Readiness Assessment Questionnaire (TRAQ) scores of the two groups. The secondary outcomes included the differences between the Self-Efficacy Scale for Children and Adolescents with Asthma and Mind the Gap scores of the two groups. The outcomes were measured at two different time points: baseline (first assessment; Week 0) and immediately after the intervention (last assessment; Week 12). Results: In the initial evaluations, there was no significant difference between the groups in terms of the primary or secondary outcomes (p > .05). In the final assessments, the TRAQ (Z = -4.740, p < .001) and Self-Efficacy Scale for Children and Adolescents with Asthma (t = 6.344, p < .001) scores of the intervention group were found to be significantly higher than the scores of the control group, while their Mind the Gap Scale scores were significantly lower (t = 6.146, p < .001). Conclusion: It was determined that the educational intervention integrated with pediatric care based on readiness for transition from pediatric care to adult care was effective in increasing the transition readiness and self-efficacy of the adolescents.
Keywords: Asthma; Health Education; Healthcare Transition; Transfer Of Care